Dog Demography, Animal Bite Management and Rabies Knowledge-Attitude and Practices in the Awash Basin, Eastern Ethiopia. - Rea Tschopp; Shiferaw Bekele; Abraham Aseffa (Public Library of Science (PLoS), 2016)
BACKGROUND:Rabies is a viral zoonosis that has been described in limited numbers of studies in Ethiopia at large and among pastoralists in particular. This study assessed dog demography, bite wound prevalence and management, potential risk factors of disease transmission and knowledge attitude practice towards rabies among urban dwellers, pastoralists and health workers in Awash, Eastern Ethiopia. METHODOLOGY:Information was collected by means of structured questionnaires and interviews and through medical and official records from the Agricultural and Health bureaus. PRINCIPAL FINDINGS:Respondents totaled 539 (471 urban, 49 pastoralists, 19 medical). Dog(s) were owned in 33% urban and 75.5% pastoralist households respectively. Mean dog number per dog owning household was 1.50 (95%CI: 1.40-1.60) in urban and 2.05 (95%CI: 1.51-2.60) in pastoralists sites. Human Dog Ratio in Metahara was 4.7:1. No bite wounds records were kept in medical facilities, where staff recalled around 100 bites per year, 2/3 being in adults. Over 90% of the respondents claimed knowing rabies but up to 79.2% pastoralist did not know how dogs acquire the disease; 37.3% urban and 23% pastoralist did not know the symptoms of rabies in dogs; 36% urban and 44% pastoralists did not know rabies symptoms in people. Eighty percent of pastoralists did not know that the disease was fatal in people if untreated. Over half (58.7%) of pastoralist respondents go to traditional healers if bitten, despite a health extension worker program in place in the study area. Knowledge gaps were also shown amidst medical staff. CONCLUSIONS:The study highlighted overall poor disease knowledge, severe under-reporting of human rabies cases, lack of record keeping and poor collaboration between the public and animal health sectors and communities in rabies control.